Comparison of total‐etch, self‐etch, and selective etching techniques on class V composite restorations prepared by Er:YAG laser and bur: a scanning electron microscopy study. Issue 10 (29th July 2016) - Ozel, Emre; Tuna, Elif Bahar; Firatli, Sonmez; Firatli, Erhan
Abstract: The purpose of this study was to compare total‐etch, self‐etch, and selective etching techniques on the marginal microleakage of Class V composite restorations prepared by Er:YAG laser and bur. Class V cavities prepared on both buccal and lingual surfaces of 30 premolars by Er:YAG laser or bur and divided into six groups. The occlusal margins were in enamel, and the cervical margins were in cementum. Group‐1: bur preparation(bp)+Adper Single Bond 2 (ASB)+Filtek Z550 (FZ); Group‐2: laser preparation(lp)+(ASB)+(FZ); Group‐3: bp + Clearfil S3 Bond Plus (CSBP)+(FZ); Group‐4: lp+(CSBP) (FZ); Group‐5: bp + acid etching+(CSBP)+(FZ); Group‐6: lp + acid etching+(CSBP)+(FZ). All teeth were stored in distilled water at 37°C for 24 hr, and then thermocycled 1000 times (5–55°C). Five teeth from each group were chosen for the microleakage investigation, and two teeth for the scanning electron microscope evaluation. Teeth which were prepared for the microleakage test were immersed in .5% methylene blue dye for 24 hr. After immersion, the teeth were sectioned and observed under a stereomicroscope for dye penetration. Data were analyzed using Kruskal–Wallis and Mann–Whitney U tests ( p  < .05). More microleakage was observed in the cervical regions compared to the occlusal regions in Groups 3, 5, and 6, respectively ( p  < .05). There is no statistically significant difference in Groups 1, 2, and 4, in terms of cervical regions versus occlusal regions ( p  > .05). No significant differences were observed among any groups in terms of occlusal and cervical surfaces, separately ( p  > .05). Different etching techniques did not influence microleakage of Class V restorations prepared by Er:YAG laser and bur.